2021
DOI: 10.3390/universe7070238
|View full text |Cite
|
Sign up to set email alerts
|

Ellis–Bronnikov Wormholes in Asymptotically Safe Gravity

Abstract: In this paper, we investigate the simplest wormhole solution—the Ellis–Bronnikov one—in the context of the asymptotically safe gravity (ASG) at the Planck scale. We work with three models, which employ the Ricci scalar, Kretschmann scalar, and squared Ricci tensor to improve the field equations by turning the Newton constant into a running coupling constant. For all the cases, we check the radial energy conditions of the wormhole solution and compare them with those that are valid in general relativity (GR). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…These features have been shown in Figure 1 for the squared Ricci tensor model, and in Figure 2 for the Kretschmann model, where we basically have the same behavior. These results are analogous to those found for other asymptotically flat wormholes, such as Ellis-Bronnikov one, studied in [71], where the authors showed that is the possible that the radial energy conditions are satisfied nearby the throat, but the presence of exotic matter, such as phantom or quintessence, is always necessary.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These features have been shown in Figure 1 for the squared Ricci tensor model, and in Figure 2 for the Kretschmann model, where we basically have the same behavior. These results are analogous to those found for other asymptotically flat wormholes, such as Ellis-Bronnikov one, studied in [71], where the authors showed that is the possible that the radial energy conditions are satisfied nearby the throat, but the presence of exotic matter, such as phantom or quintessence, is always necessary.…”
Section: Discussionsupporting
confidence: 84%
“…As we can see, the quantum improvement leads to the inevitable presence of phantomlike matter regions as source to generate the wormhole spacetime. These results are very similar with the Ellis-Bronnikov wormhole [72][73][74] case, which was studied by Alencar et al [71]. They found that for the ASG context the radial energy conditions are satisfied in the throat for a range of values of r 0 , and for this is necessary a exotic matter, like quintessencial fluid threading the wormhole throat.…”
Section: Schwarzschild Wormhole Solution In Asgsupporting
confidence: 86%
See 1 more Smart Citation
“…In [49], the authors have shown that improved pseudospherical wormholes could be traversible with nonexotic matter, while spherical ones could not. In [50], the authors investigated the Ellis-Bronnikov wormhole solution in the ASG context and it was showed that, for a perfect fluid, it is not possible to get a traversible Ellis-Bronnikov wormhole without exotic matter, and in order to be traversible the wormhole requires very exotic phantom-like matter in some regions of the modified spacetime and even at the throat. And more recently, it was showed in [51] that Schwarzschild-like wormholes exhibit the possibility of having nonexotic matter as source for certain values of the radial coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…Classical and quantum-modified theories of gravity, applied in the study of wormholes, were quite discussed in the literature [27][28][29][30][31]. Still concerning such objects, a class of modified theories as those embodying background fields coupled to the gravity, with spontaneously Lorentz symmetry breaking, were analyzed in Refs.…”
Section: Introductionmentioning
confidence: 99%